Analysis of The Nature of Science in Class IV Thematic Curriculum 2013 Books - Muhammad `Izza Mahendra Anharuddin; Siti Fatonah (Jurnal Penelitian Pendidikan IPA, 2023)
This study was aim to analyse science as a process skill, products/content, and attitudes on students’ book thematic at 4th grade Theme 3 Curriculum 2013. The design of this study was qualitative with the type of content study research. The data was collected through documentation. Data analysis techniques through reduction, presentation and drawing conclusions. The results showed that science as a process skill, products/content and attitudes was available on that book, but the aspect of science process skill, science as product and science as hat attitudes was not complete. Science as a product/content found in this book merely on fact, concept, and principle. Science as attitudes found on this book are honest, open minded, responsible, objective, cooperative, critical thinking, curiosity, careful, discipline, care for environment. Science as a process found of this book are still limited in: observing, classifying, concluding, and communicating